2015
DOI: 10.17235/reed.2015.3926/2015
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of metronidazole versus placebo in pain control after hemorrhoidectomy. Results of a controlled clinical trial

Abstract: Introduction: Hemorrhoidal disease occurs in 50% of people aged > 40 years and is the most common reason for anorectal surgery. Pain is the main complication. Multiple topical and systemic drugs have been investigated for pain control, but there is no ideal treatment. Metronidazole has been shown to decrease postoperative pain but is not used widely.Objective: To evaluate the effect of oral metronidazole versus placebo and to assess postoperative pain following hemorrhoidectomy.Material and methods: Controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 30 publications
(39 reference statements)
0
33
0
Order By: Relevance
“…demonstrated a reduction in pain on days 1 and 4 but found no difference on days 5–7 and thus concluded that metronidazole did not reduce postoperative pain. These differences are surprising given the significant overlap in the studies considered by these two reviews and we would suggest that the differences are probably the result of several methodological differences between the two analyses.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…demonstrated a reduction in pain on days 1 and 4 but found no difference on days 5–7 and thus concluded that metronidazole did not reduce postoperative pain. These differences are surprising given the significant overlap in the studies considered by these two reviews and we would suggest that the differences are probably the result of several methodological differences between the two analyses.…”
Section: Discussionmentioning
confidence: 72%
“…Of the nine papers progressing to full text review one was excluded for not providing data on metronidazole alone as an intervention. A total of eight RCTs [17][18][19][20][21][22][23][24] were therefore included in this review with an aggregated population of 437 patients. Three of the studies used closed approaches [18,19,24] with the remaining five [17,[20][21][22][23] using open haemorrhoidectomy approaches.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations